The significance of the detoxification system disorders in fibrogenesis in Chronic Viral Hepatitis С in children - E. A. Galova; V. V. Krasnov (LLC "Diagnostics and Vaccines", 2021)
Aim: to determine the relationship between of levels»protoxic» metabolites and «profibrotic» metabolites in the blood serum in children with chronic viral hepatitis C (HCV).Material and methods: the authors examined 54 children 14.0[6,0] years old with HCV. The blood serum levels of Molecules of average mass, Oligopeptides, Alcohol dehydrogenase, Glutathione-S-transferase, Ammonia, Arginase and Collagen IV have been studied.Results: A high level of «protoxic» metabolites in the blood serum was associated with a disorder of their elimination. The relationship with viral replication and biochemical hepatitis activity has not been identified. The collagen IV blood serum level was correlated with the accumulation and elimination of «protoxic» metabolites: R = 0.63, F = 5.19, p = 0.018.Conclusion: The level of collagen IV in the children's blood serum was associated with the accumulation and the elimination of «protoxic» metabolites.